PERBANDINGAN EFEK PERASAN DAGING DAUN LIDAH BUAYA (Aloe vera L.) DAN POVIDONE IODINE TERHADAP EKSPRESI VEGF DAN JUMLAH LUMEN PEMBULUH DARAH TIKUS WISTAR DENGAN LUKA SAYAT - Moch. Saifudin; Merlita Herbani; Diah Andriana (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: Incision wound is disorders of skin structure that causes sensory dysfunction and the delay in this process may cause increasing the patient’s morbidity. Some alternative treatment to increase wound healing is by using herb such as Aloe vera. Therefore, the study to know the effect of Aloe vera on wound healing process by measuring the VEGF expression and number of blood vessels is needed.Method: 24 male Wistar rats aged 2-3 months divided into 4 groups, (1). K + (povidone iodine) group, (2). The treatment group given the taste of aloe with 20% concentration (KP1), (3). 40% concentration (KP2) and (3). 80% concentration (KP3) at a dose of 0.5 gr/rat/day topically for 6 days. VEGF expressions are measured using immunohistochemistry (IHK) staining and blood vessels using Hematoxylin Eosin (HE). Data obtained by statistical analysis using SPSS version 17 with a signification level p < 0.05Result: Effect of Aloe vera juice on VEGF expression in KP+, KP1, KP2, KP3 goup were (1.41±1.79), (1.40±2.09), (1.42±1.24), and (1.44±1.52) with signification value (p>0,05). Effect of Aloe vera juice on the number of blood vessel lumen in KP+, KP1, KP2, KP3 goup were (14.7±4,94), (17.16±4,67), (25.53±5.54), dan (33.9±11.82) with signification value (p<0,05).Conclusion: Aloe vera juice affect on the number of blood vessel lumen. Further research in need to know the active compound in Aloe vera that has wound healing effectKeywords: Incision Wound, Aloe vera L., vascular endoothelial growth factor (VEGF), Blood vessels